PRODUCTION OF TECHNOLOGY FOR OBTAINING OIL FROM PEANUT KERNELS AND REFINING THE OIL OBTAINED IN SHORT CYCLES - Voqqosov, Zuxriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the extraction of oil from peanut kernels by pressing method, the production of reduced cycle refining technology in the case of choosing the necessary refining methods, and the selected oil of Rakhbar, Salamat , Mumtoz , Qibra-4 varieties according to the quality indicators of the obtained oil according to the standard requirements. the amount varies from 42.5% to 55.3% and was found to contain oleic (35.10%-42.66%) and linolenic acid (30.53%-40.86%). At the same time, it contains a large amount of α -, γ - and δ -tocopherol and β -sitosterol, stigmasterol, campesterol. The physicochemical parameters evaluated were as follows: acid value (0.11-2.74 KOHg/ mg) and peroxide value (1.94-5.55 mmol/kg) analysis is detailed